Abstract 276: CT versus MR based imaging for ischemic stroke triage: effect on workflow during contrast shortage - Rami Fakih (Stroke: Vascular and Interventional Neurology)
Introduction We assessed the feasibility and effectiveness of using magnetic resonance (MR) imaging as a substitute for computed tomography (CT) angiography and perfusion for triaging ischemic stroke patients during the national shortage of iodinated contrast medium between May 4th to July 17th 2022. Methods We compared the rates of intravenous tissue plasminogen activator treatment (IVT) and endovascular thrombectomy (EVT), changes in treatment times, and patient outcomes (defined by modified Rankin Scores (mRS) at discharge) before (4 months period) and after (3 months period) transitioning from CT angiography (CTA) and perfusion (CTP) to Fast MRI imaging. Results We analyzed 241 patients in the CT‐based group and 166 patients in the MR‐based group. EVT was performed on almost twice as many patients in the CTA/CTP group (12%) compared to the Fast MRI group (6.6%), but this difference was not statistically significant (p=0.07). Workflow processing time showed no significant difference, with similar time intervals for door‐to‐needle, door‐to‐interventioanal radiology suite, door‐to‐puncture, and door‐to‐first pass. However, the CTA/CTP group exhibited a trend towards faster overall times. Both groups had similar rates of mRS 0‐2 at discharge (41.9% vs 43%, p=0.82). Conclusion We observed a non‐significant reduction in the rate of EVT during the period of MRI substitution secondary to the iodinated contrast medium shortage, although treatment times and patient outcomes were similar.